TURKISH-GERMAN TRADE RELATIONS 1993-2005 A.D. - Alaw Al-Samarraie, Dr. Ahmed Mahmood; Hamzah Hussein, Dr. Mohammad; Elham Abdel, Dr. Manhal (The journal of contemporary issues in business and government, 2022)
The Turkish-German relations enjoy strong common interests between the two parties, especially in the economic field, as the Turks consider the presence of the Germans important in their economic strategies, in addition to being Turkey’s gateway to rapprochement with the European Union. Common interests prompted both countries to seek to overcome the political tensions that sometimes arise between them. Germany has worked hard to maintain the exports of German companies to Turkey at a high level, while the Turks are seeking to continue the activity of their industrial sectors in supplying Turkish exports to Germany, as well as benefiting from German investments presented to the Turkish economy.